RANCANG BANGUN APLIKASI PENCARIAN PENGAJAR LES MUSIK PADA STARTUP FIRSTUDIO DENGAN METODE MATCHING PROFILE - Nugraha, Firmansyah Rizkiawan; Sutomo, Erwin; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
Firstudio is a startup that is engaged in the music field. Firstudio is engaged in music by providing online studio booking facilities and online teacher searches. From identifying and interviewing the community, instructors, students to the online search process for teachers. The difficulty in finding instructors for music lessons is a major problem that occurs in the community. By using the teacher's matching profile method and students can choose the criteria according to their wishes. In addition students can also directly choose instructors who have been recommended based on criteria. Of the several porblems that have been described, the solution given is the presence of a teacher search application with matching profile method. With this application, it is expected to make it easier for students to find instructors who are in accordance with the required criteria.